Identifikasi Kebutuhan Belajar pada Masa Pandemi Covid-19 di SD Negeri Pakulonan 1 Tangerang - Putri, Adelia Rohmadona; Azahra, Azma; Septiliana, Citra; Pihimayatillah, Wapik (ANWARUL, 2022)
The research was about the analysis of teacher needs in the implementation of online learning process during the pandemic at SD Negeri Pakulonan 1 Tangerang the academic year of 2020/2021. The background of this research because of the learning transition from conventional to online learning as an impacted of COVID-19 pandemic. The objective of the research to know ideal needs in the implementation of online learning for the primary school teachers. The design of the research used qualitative method with case study approach. The data collecting was obtained through interview with teachers at the grade of III- 1, VI-2, and school supervisor, documentation, and parent questionnaire. The result of this research indicated that the teacher at the grade of III-1 and VI-2 achieved the ideal needs for implementation of online learning. The needs of teachers used were: (1) facility of online learning; (2) media of online learning, like applications and features; and (3) model variation of online learning. In the future, the teacher expect the developing of facility, media, and model variation of online learning. The teacher also hoped the role of government to introduce the applications the supported by education quota and give attention about the available of internet access.